2017
DOI: 10.1016/j.bjorl.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Intrasphenoid septations inserted into the internal carotid arteries: a frequent and risky relationship in transsphenoidal surgeries

Abstract: The frequency of intrasphenoid septations in the ICAp found is considerable. It is higher among patients with more pneumatised sinuses. This finding justifies an appropriate pre-operative study, and careful attention must be paid during transsphenoidal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The inter-sphenoid septum (ISS) is an important anatomical landmark within the SS; it varies in number and point(s) of insertion on the sinus wall but often inserting on the bony covering of the ICA. Previously reported the prevalence of ISS insertion into ICA bony covering ranges from 4.9% to 89%151920 and in our study, the prevalence is 31.6%. During endoscopic surgery, the septum must be removed to expose the sella floor, thereby creating adequate surgical corridor 20.…”
Section: Discussionsupporting
confidence: 56%
“…The inter-sphenoid septum (ISS) is an important anatomical landmark within the SS; it varies in number and point(s) of insertion on the sinus wall but often inserting on the bony covering of the ICA. Previously reported the prevalence of ISS insertion into ICA bony covering ranges from 4.9% to 89%151920 and in our study, the prevalence is 31.6%. During endoscopic surgery, the septum must be removed to expose the sella floor, thereby creating adequate surgical corridor 20.…”
Section: Discussionsupporting
confidence: 56%
“…But it often inserts on the bony covering of the ICA. In previous studies the prevalence of inter sphenoid septum insertion into the bony covering of ICA in between 4.9%-89% and in our study the prevalence is (30,31,32) 31%(n=31). While performing endoscopic trans sphenoidal surgery, the septa should be removed for exposing oor of sella turcica, thereby creating adequate surgical corridor .And it should be done with (32) extreme caution and without making avulsion fracture of the septum.…”
supporting
confidence: 60%
“…This figure is quite similar to the study of CT scan of 421 patients done by Ramalho CO et al, who found prevalence of 52%. 19 Fernandez-Miranda et al, showed radiologic prevalence of 85% among patients with at least one septation attached to carotid protuberance. 20 Other studies have quoted lower figures in this respect.…”
Section: Pattern Of Septationmentioning
confidence: 99%